2020
DOI: 10.1002/ecy.2997
|View full text |Cite
|
Sign up to set email alerts
|

Highly invasive tree species are more dependent on mutualisms

Abstract: Citation: Moyano, J., M. A. Rodriguez-Cabal, and M. A. Nuñez. 2020. Highly invasive tree species are more dependent on mutualisms. Ecology 101(5):Abstract. Why some species become invasive while others do not remains an elusive question. It has been proposed that invasive species should depend less on mutualisms, because their spread would then be less constrained by the availability of mutualistic partners. We tested this idea with the genus Pinus, whose degree of invasiveness is known at the species level (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 95 publications
3
28
0
1
Order By: Relevance
“…Despite empirical support for the ideal weed hypothesis, there is evidence that suggests some invasive plants may be more reliant on mutualisms than expected. In a recent meta-analysis based on data of Pinus seedling growth with and without mycorrhizal fungi, we found that species that are more invasive were more dependent on this mutualism (Moyano et al 2020). According to this study, Pinus species with higher invasiveness and lower seed mass had a higher growth response to ectomycorrhizal fungi (EMF) inoculation.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Despite empirical support for the ideal weed hypothesis, there is evidence that suggests some invasive plants may be more reliant on mutualisms than expected. In a recent meta-analysis based on data of Pinus seedling growth with and without mycorrhizal fungi, we found that species that are more invasive were more dependent on this mutualism (Moyano et al 2020). According to this study, Pinus species with higher invasiveness and lower seed mass had a higher growth response to ectomycorrhizal fungi (EMF) inoculation.…”
Section: Introductionmentioning
confidence: 89%
“…Following the results of Moyano et al (2020), we predicted that species with higher invasiveness would show higher responsiveness to EMF inoculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EcM plant species form a disproportionately high share of alien trees globally, and many of them are regarded as the most severe invaders [ 31 – 34 ]. Recently, Moyano et al [ 63 ] provided evidence that alien EcM plants that rely more on EcMF are more prone to become invasive in introduced regions. Therefore, our study, which provides the most comprehensive overview of strategies that alien EcM plants adopted to establish a mycorrhizal partnership in regions to which they were introduced, represents a substantial step forward in understanding the mechanisms of EcM plant naturalization.…”
Section: Discussionmentioning
confidence: 99%
“…Introduced native seedlings (via restoration) may not succeed if the native microbial communities are not introduced concurrently, especially those associated with initial colonization. Restoration efforts often involve controlling invasive species (Weidlich et al 2020), which may rely on mutualists (Vogelsang & Bever 2009; Moyano et al 2020), but little is known about the consequences of having exotic soil microbiota in areas where exotic plants have been removed. For ECMs, interactions between native plants and exotic fungi do not necessarily cease after the removal of exotic plant species (Lofgren et al 2018).…”
Section: Recognizing the Roles Of Ectomycorrhizae And Overcoming Knowmentioning
confidence: 99%